Pneumatically-driven stretching machine for ankle dorsiflexion: safety concepts and effectiveness test involving healthy young subjects - Shiraishi, Yuma; Okamoto, Shogo; Yamada, Naomi; Inoue, Koki; Akiyama, Yasuhiro; Yamada, Yoji (ROBOMECH journal, 2020)
Stretching is a major treatment for restoring the ankle range of motion while decreasing the ankle stiffness. An automatic stretching machine can provide long-term continual stretching at home. However, no commercial stretching machines are currently available, and therefore, no safety guidelines exist for them. In this study, we prototyped a stretching machine using a chassis from a commercial foot exerciser for preventing disuse syndrome, and then proposed three safety concepts as general requirements for stretching machines. The concepts were determined based on risk assessments, which included (1) preventing excessive force from being applied to the foot, (2) responding to the ankle stiffness and the range of motion of each different individual, and (3) preventing unintended operations by the user. The above concepts allowed us to develop a stretching machine taking into account safety measures. Further, the stretching effect of the prototype was tested on sixteen healthy young subjects ( 22.3 ± 3.6 years ). We found that the passive resistance of the subjects at specific dorsiflexion angles decreased significantly after stretching the ankle using the prototyped machine.